2020
DOI: 10.1177/0954406220916538
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic characteristics research of a water lubricating axial piston pump

Abstract: A water lubricating axial piston pump (WLAP) is one of the key components in water hydraulic systems. However, the characteristics of water, including low viscosity, strong corrosiveness, and easy vaporization, results in the increase of friction and wear of pairs, and the increase of temperature. Compared with oil pumps, the thermodynamic characteristic of WLAP is more serious. In this paper, the integrated thermodynamic model of WLAP, which includes heat generation of pairs and heat conduction of water and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…On the foundation of former research about the temperature distribution, Dirichlet condition is imposed on the inner surface of the shell with a constant temperature of 350 K, which is the maximum value of internal elements. With an ambient temperature of air ranges from 273.15 K to 323.15 K, the radiation heat transfer takes up less than 3% of the general heat dissipation [25]. To put it another way, the method of convection transfers more heat than radiation.…”
Section: Mesh and Boundary Conditionsmentioning
confidence: 99%
“…On the foundation of former research about the temperature distribution, Dirichlet condition is imposed on the inner surface of the shell with a constant temperature of 350 K, which is the maximum value of internal elements. With an ambient temperature of air ranges from 273.15 K to 323.15 K, the radiation heat transfer takes up less than 3% of the general heat dissipation [25]. To put it another way, the method of convection transfers more heat than radiation.…”
Section: Mesh and Boundary Conditionsmentioning
confidence: 99%
“…Wu Kaipeng et al [24] performed numerical simulations of the full cavitation flow field of automotive electronic water pumps at 25 • C, 50 • C, and 70 • C. Li Wei et al [25] studied the cavitation performance of engine-cooling water pumps at different temperatures and found that as the temperature increased from 25 • C to 70 • C, the cavitation area within the impeller expanded. Li Donglin et al [26] developed a thermodynamic model for a water-lubricated axial piston pump. Their calculations indicate that the pump cannot operate normally when the temperature exceeds 90 • C.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Due to the high working pressure, the structure of the piston pump is generally adopted, and the suction and discharge of the pump are controlled through the port valves. 8,9 O-rings are usually used as static seals on piston pumps due to their simple structure and low cost. For a static seal ring, its working state is generally more straightforward than that of a dynamic seal ring.…”
Section: Introductionmentioning
confidence: 99%
“…3–7 Due to the high working pressure, the structure of the piston pump is generally adopted, and the suction and discharge of the pump are controlled through the port valves. 8,9…”
Section: Introductionmentioning
confidence: 99%